2002
DOI: 10.1667/0033-7587(2002)157[0003:apiiit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Particle-Induced Increases in the Radioresistance of Normal Human Bystander Cells

Abstract: Numerous investigators have reported that direct exposure of cells to a low dose of ionizing radiation can induce a condition of enhanced radioresistance, i.e. a "radioadaptive" response. In this report, we investigated the hypothesis that a radioadaptive bystander effect may be induced in unirradiated cells by a transmissible factor(s) present in the supernatants of cells exposed to a low dose of alpha particles. Normal human lung fibroblasts (HFL-1) were irradiated with 1 cGy of alpha particles and their sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 33 publications
5
75
1
1
Order By: Relevance
“…Xu et al (1996). can reduce the effects of the damaging system. Using doses where bystander effects have been shown to occur, such experiments have been reported by Iyer and Lehnert (2002a). They showed that medium taken from human lung fibroblasts exposed to 10 mGy of α-radiation increased clonogenic survival of other cells exposed to 100 mGy of α-particles.…”
Section: Adaptive Responses Against Damaging Bystander Effectsmentioning
confidence: 87%
“…Xu et al (1996). can reduce the effects of the damaging system. Using doses where bystander effects have been shown to occur, such experiments have been reported by Iyer and Lehnert (2002a). They showed that medium taken from human lung fibroblasts exposed to 10 mGy of α-radiation increased clonogenic survival of other cells exposed to 100 mGy of α-particles.…”
Section: Adaptive Responses Against Damaging Bystander Effectsmentioning
confidence: 87%
“…Given that the multiple markers that have been used to study the BSE, that is, micronuclei formation (Yang et al, 2007), clonogenic survival (O'NeillMehlenbacher et al, 2007), apoptosis (Grifalconi et al, 2007) and sister chromatid exchange (SCE) (Nagasawa et al, 2005) (Figure 1), are themselves considered to be detrimental, it has been assumed that the BSE is harmful to neighboring cells. However, it has also been proposed that the BSE may actually be beneficial at a tissue level; cells exposed to a bystander signal are more radioresistant to subsequent IR-induced damage indicative of an adaptive response (Iyer and Lehnert, 2002). It is also noteworthy that of these markers, only SCE frequency is not significantly influenced by direct low-LET (for example, g-ray) radiation exposure (Ardito et al, 1980), making SCE an attractive marker of the BSE.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in protein levels of AP endonuclease, a redox and DNA base excision repair protein, was also measured in bystander cells but not in directly irradiated cells. The promitogenic response was associated with an increase in cloning efficiency (Iyer and Lehnert, 2002). …”
Section: Distant 'Bystander' Effects: Medium Transfer Experimentsmentioning
confidence: 99%
“…The results from different laboratories, however, are not entirely consistent. Some workers report that incubation with such a conditioned medium leads to a reduction in cloning efficiency of the recipient cells (Lyng et al, 2002;Sawant et al, 2002), while others find that it is enhanced (Iyer and Lehnert, 2002) or dependent on cell type (Mothersill and Seymour, 1997). The effect of irradiated medium alone is particularly controversial.…”
Section: Distant 'Bystander' Effects: Medium Transfer Experimentsmentioning
confidence: 99%